Segmented evolution and exploration targets of the Cambrian platform margin in the Manxi area, Tarim Basin - Zongquan Hu; Fan Feng; Chengming Fang; Zicheng Cao; Tieyi Wang; Kangkang Guo; Yang Li; Shi Wang (Energy Geoscience)
The Cambrian platform margin in the Tarim Basin boasts favorable source-reservoir-cap assemblages, making it a significant target for hydrocarbon exploration in ultra- to extra-deep facies-controlled formations. Of the three major basins in western China, Tarim is the only basin with large-scale platform margin where no exploration breakthrough has been achieved yet. This study determines the vertical and lateral differential evolution of the platform margin (in the Manxi area hereafter referred to as the Cambrian Manxi platform margin) through fine-scale sequence stratigraphic division and a segmented analysis. The platform margin can be divided into the Yuqi, Tahe, Shunbei, and Gucheng segments, from north to south, based on the development of different ancient landforms and the evolutionary process of the platform. The Yuqi and Shunbei segments exhibit relatively low-elevation ancient landforms. Both segments were in a submarine buildup stage during the Early Cambrian, resulting in overall limited scales of their reservoirs. The Gucheng segment features the highest-elevation ancient landforms and accordingly limited accommodation spaces. As a result, the rapid lateral migration of high-energy facies zones leads to the development of large-scale reservoirs with only limited thicknesses. In contrast, the Tahe segment, exhibiting comparatively high-elevation ancient landforms, is identified as the most favorable segment for the formation of large-scale reservoirs. The cap rocks of the platform margin are dominated by back-reef dolomitic flats and tight carbonate rocks formed in transgressive periods. A comprehensive evaluation of source rocks, reservoirs, and cap rocks indicates that the Tahe segment boasts the optimal hydrocarbon accumulation conditions along the platform margin. In this segment, the Shayilike Formation transgressive deposits and the high-energy mound-shoal complexes along the platform margin of the Wusonggeer Formation constitute the optimal reservoir - cap rock assemblage, establishing this segment as the most promising target for hydrocarbon exploration in the platform margin.